Missão Aspirapó: A digital game for teaching and learning graphs - Santos, Matheus V.; Braga, Andrei de A. S.; Grando, Felipe; Pegoraro, Raquel A. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: Currently, the integration of information and communication technologies into daily life directly influences teaching models at different educational levels. Additionally, there are well-known educational challenges in the field of computing, resulting in high rates of failure and dropout. Among these challenges, students’ difficulties with the subfield of graphs stand out. Objective: This study aims to assess the impact of using a digital educational game on graphs in teaching and learning this topic. Hence, we present Missão Aspirapó, a mobile digital game for Android developed with this purpose. Methodology or Steps: The methodologies Learning Design and Programa de Avaliação de Jogos Digitais Educacionais were used, respectively, for the creation and evaluation of the game. Results: The results indicate that the game has a learning potential between high and very high, making it a viable educational tool, but with some opportunities for improvement.